Pengembagan Sistem Informasi Pengarsipan Data Dosen Pada Lembaga Penelitian Universitas Ichsan Gorontalo - Muhammad Asri (Teknik Elektro - Universitas Ichsan Gorontalo, 2017)
Information system at Research Institute (Lemlit) of University Ichsan Gorontalo which currently has developed, yet sufficiently unable to meet the expectations of the lecturers in facilitating the ease of archiving related to the research documents. As for that we need a specific new features with quick access and easy to use. The purpose of this study is to facilitate the lecturers to archiving data documents related to the research so as to reduce the risk of data loss. So that the user can be more easily to applied, then the information system due to built using PHP programming language, database using MySQL, and website portal are designed using Drupal version 7.5 with Content Management System (CMS) system. The design until the development of information system Lemlit University Ichsan Gorontalo is a form of adding more new features to facilitate the lecturers in filling form biodata, research proposal form, results form, and research journals as well as display document downloads from Lemlit or research assignment letter. The system above can be accessed through various media such as internet network through Personal Computer, Laptop or Smartphone. Keywords: Information system, archiving, Research Institute